Comparing pharmacists versus allergists in low-risk penicillin allergy delabelling: The Hong Kong Penicillin Allergy Pharmacist Initiative (HK-PAPI) - James K.Y. Hooi, MBChB; Marshall C.H. Low, BPharm; Jonathan C.L. To, BPharm; Hugo W.F. Mak, MBBS; Mandy M. Choi, BPharm; Chris C.P. Tam, BPharm; Raymond W.M. Mak, MSc; Vincent K.C. Wong, MPharm; Timo C.C. Chan, MClinPharm; Andrew W.T. Li, MClinPharm; Charlie C.Y. Mak, MClinPharm; Valerie Chiang, MBBS; et al. (World Allergy Organization Journal)
Background: Mislabelled penicillin allergies are associated with a myriad of adverse outcomes and development of anti-microbial resistance. With the overwhelming need for specialist allergy services, pharmacist initiatives such as the Hong Kong Penicillin Allergy Pharmacist Initiative (HK-PAPI) have been advocated. However, evidence of their effectiveness, safety and impact on health-related quality-of-life (HR-QoL) are lacking.To assess and compare the effectiveness, safety and improvements on HR-QoL of pharmacists vs allergists in a pilot low-risk penicillin allergy delabelling initiative. Methods: All adult patients referred for low-risk penicillin allergy were randomized and evaluated by either pharmacists or allergists in a 1:3 ratio. Outcomes and changes in Drug Hypersensitivity Quality of Life Questionnaire (DrHy-Q) scores were compared. Results: Of 323 patients referred, 96.3% (311/323) completed penicillin allergy evaluation (pharmacists: 83 [24.3%] vs allergists: 228 [66.7%]). Overall, 93.6% (291/311) were delabelled with no difference between evaluations by pharmacists and allergists (92.8% vs 93.9%, p = 0.729). There were no severe or systemic reactions in either cohort. Patients evaluated by either pharmacists (43.4 [SD:29.1] to 10.5 [SD:5.93], p < 0.001) or allergists (37.2 [SD:22.2] to 29.1 [SD:22.4], p < 0.001) reported improved HR-QoL as reflected by DrHy-Q scores. However, absolute changes in DrHy-Q scores were significantly greater among patients evaluated by pharmacists compared to those by allergists (−24.6 [SD:25.1] vs −9.19 [SD:13.7], p < 0.001). Conclusions: Evaluations and delabelling by pharmacists (vs allergists) were comparably effective and safe among patients with low-risk penicillin allergy. Moreover, patients evaluated by pharmacists even reported significantly greater improvements in HR-QoL, highlighting the potential of multidisciplinary allergy initiatives.